Effect of milk pasteurisation and of ripening in a cave on biogenic amine content and sensory properties of a pecorino cheese. (October 2016) - Torracca, Beatrice; Pedonese, Francesca; López, Maria Belén; Turchi, Barbara; Fratini, Filippo; Nuvoloni, Roberta
Abstract: Ewes' milk cheeses were evaluated with respect to the influence of pasteurisation and of ripening in a cave on the biogenic amine (BA) content and sensory properties. Both factors significantly influenced the BA content, with higher BA concentrations (on average >1500 mg kg −1 total; 850 mg kg −1 of tyramine) in cheeses manufactured with raw milk and partly ripened in a cave. Milk pasteurisation effectively limited BA formation both qualitatively and quantitatively, but still allowed the accumulation of notable BA levels in cave ripened cheeses. Thus, milk pasteurisation seems not sufficient to guarantee low BA levels in cheeses, particularly when the cheesemaking process employs unconventional ripening conditions. Discriminatory sensory testing showed that the different types of experimental cheeses had detectable sensory differences, although descriptive sensory analysis highlighted few statistically significant differences, mainly due to the effect of the ripening conditions on some texture characteristics and on the aroma intensity.